Maintaining Tissue Perfusion in High-Risk Surgical Patients: A Systematic Review of Randomized Clinical Trials - Gurgel, Sanderland T.; do Nascimento, Paulo [UNESP] (Lippincott Williams & Wilkins, 2011)
BACKGROUND: Surgical patients with limited organic reserve are considered high-risk patients and have an increased perioperative mortality. For this reason, they need a more rigorous perioperative protocol of hemodynamic control to prevent tissue hypoperfusion. In this study, we systematically reviewed the randomized controlled clinical trials that used a hemodynamic protocol to maintain adequate tissue perfusion in the high-risk surgical patient.METHODS: We searched MEDLINE, Embase, LILACS, and Cochrane databases to identify randomized controlled clinical studies of surgical patients studied using a perioperative hemodynamic protocol of tissue perfusion aiming to reduce mortality and morbidity; the latter characterized at least one dysfunctional organ in the postoperative period. Pooled odds ratio (POR) and 95% confidence interval (CI) were calculated for categorical outcomes.RESULTS: Thirty-two clinical trials were selected, comprising 5056 high-risk surgical patients. Global meta-analysis showed a significant reduction in mortality rate (POR: 0.67; 95% CI: 0.55-0.82; P < 0.001) and in postoperative organ dysfunction incidence (POR: 0.62; 95% CI: 0.55-0.70; P < 0.00,001) when a hemodynamic protocol was used to maintain tissue perfusion. When the mortality rate was >20% in the control group, the use of a hemodynamic protocol to maintain tissue optimization resulted in a further reduction in mortality (POR: 0.32; 95% CI: 0.21-0.47; P < 0.00,001). Monitoring cardiac output with a pulmonary artery catheter and increasing oxygen transport and/or decreasing consumption also significantly reduced mortality (POR: 0.67; 95% CI: 0.54-0.84; P < 0.001 and POR: 0.71; 95% CI: 0.57-0.88; P < 0.05, respectively). Therapy directed at increasing mixed or central venous oxygen saturation did not significantly reduce mortality (POR: 0.68; 95% CI: 0.22-2.10; P > 0.05). The only study using lactate as a marker of tissue perfusion failed to demonstrate a statistically significant reduction in mortality (OR: 0.33; 95% CI: 0.07-1.65; P > 0.05).CONCLUSIONS: In high-risk surgical patients, the use of a hemodynamic protocol to maintain tissue perfusion decreased mortality and postoperative organ failure. Monitoring cardiac output calculating oxygen transport and consumption helped to guide therapy. Additional randomized controlled clinical studies are necessary to analyze the value of monitoring mixed or central venous oxygen saturation and lactate in high-risk surgical patients. (Anesth Analg 2011; 112: 1384-91)